2022
DOI: 10.1001/jamapediatrics.2022.3396
|View full text |Cite
|
Sign up to set email alerts
|

Association of State Child Abuse Policies and Mandated Reporting Policies With Prenatal and Postpartum Care Among Women Who Engaged in Substance Use During Pregnancy

Abstract: ImportanceSome states have implemented policies that consider substance use during pregnancy as child abuse and require mandated reporting of substance use during pregnancy. Implications of these policies for health care receipt among pregnant people who engage in substance use are unknown.ObjectiveTo examine the association of state child abuse policies and mandated reporting policies with prenatal and postpartum care among women who engaged in substance use during pregnancy.Design, Setting, and ParticipantsI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…2 A recent meta-analysis showed that approximately 3% of infected children are hospitalized. 3 Other studies demonstrated that prior to and after the emergence of variants of concern, children with COVID-19 had similar or higher risk of hospitalization, need for life-sustaining therapy, and death as those infected with influenza. 4,5 Children also are at risk of developing multisystem inflammatory syndrome in children (MIS-C), a rare but severe postinfectious complication, often after asymptomatic or mild infection.…”
Section: Immune Response To Sars-cov-2 Infection In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…2 A recent meta-analysis showed that approximately 3% of infected children are hospitalized. 3 Other studies demonstrated that prior to and after the emergence of variants of concern, children with COVID-19 had similar or higher risk of hospitalization, need for life-sustaining therapy, and death as those infected with influenza. 4,5 Children also are at risk of developing multisystem inflammatory syndrome in children (MIS-C), a rare but severe postinfectious complication, often after asymptomatic or mild infection.…”
Section: Immune Response To Sars-cov-2 Infection In Childrenmentioning
confidence: 99%
“…In fact, Austin et al 3 find that pregnant women who reported substance use and deliver in states with a child abuse and/or mandated reporting policy are less likely to receive timely prenatal care, adequate prenatal care, and postpartum care compared with women in states that have neither policy. 3 Care delays may have marked implications for access to substance use disorder treatment and services for pregnant patients and implications for neonatal abstinence syndrome, low birth weight, prematurity, and other neonatal birth outcomes.…”
Section: Mandated Reporting Of Perinatal Substance Usementioning
confidence: 99%
“…This difference has been found in both selective and universal screening programs despite similar prevalence of drug use between the 2 groups . While CPS reports can facilitate referral to substance treatment programs and social services, they can also lead to emotional, social, and legal repercussions, including termination of parental rights …”
Section: Introductionmentioning
confidence: 94%
“…[5][6][7] While CPS reports can facilitate referral to substance treatment programs and social services, they can also lead to emotional, social, and legal repercussions, including termination of parental rights. [7][8][9] Prior cross-sectional studies found that clinicians are more likely to ask Black people about substance use in pregnancy and test Black newborns for substance exposure. [10][11][12][13] A study of urine toxicology testing for hospitalized pregnant people demonstrated more frequent testing for Black and Hispanic people for reasons other than history of substance use.…”
Section: Introductionmentioning
confidence: 99%
“…These simultaneous effects can lead to discriminatory interactions, shared inculcation of pre‐conceived stereotypes, and poor health outcomes, advancing the argument that health‐related stigma should be considered a social determinant of health. Above and beyond health‐related stigma that may be activated in response to substance use in isolation, people who are pregnant may be subject to additional social mores, societal expectations around the expectations of the “good mother” and punitive policies that have been shown to result in avoidance of prenatal care, worse perinatal outcomes, and increased risk of family separation at delivery (Austin, Naumann, & Simmons, 2022; Stone, 2015).…”
Section: Unique Stigma and Discriminationmentioning
confidence: 99%